Reaksi Pasar Modal Indonesia Atas Pengumuman Kenaikan BI 7 Day Reverse Repo Rate Tanggal 19 Oktober 2023 Pada Perusahaan Yang Terdaftar Dalam LQ45 Bursa Efek Indonesia - Ida Ayu Amelia Putri; I Putu Dedy Samtika Putra; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2025)
The research aims to analyze how the Indonesian capital market reacted to the announcement of the BI 7 Day Reverse Repo Rate by comparing average abnormal return and average trading volume activity. This study, which is an event study, will be observed for ten working days, five days prior to (t-5) and five days following (t+5) the announcement. Corporations that are included in the LQ45 index are used for the study's sample. Purposive sampling methodology combined with sample determination method. The Wilcoxon signed rank test is the data analysis method applied. The average abnormal return and average trading volume activity before and after the BI 7 Day Reverse Repo Rate announcement on October 19, 2023, do not differ, according to the results. Because the event does not control the information content and strong signal when making investment decisions to purchase or sell shares, this indicates that there was no market reaction.